An Evaluation of a 9th-Grade English Coursebook (English 9) from User Teachers and Students’ Perspectives - Sertdemir, Sedanur; Polat, Ayşe Sıla; Ayyıldız, Nilay Erdem (My University, 2025)
The aim of this study was to reveal the perceptions of grade 9 English teachers and students regarding the suitability, effectiveness and quality of the English 9 textbook. In the study, the Textbook Evaluation Survey, which includes Likert-type expressions and open-ended questions for users designed by Öz (2019), with a reliability coefficient of .92, was used to collect feedback from teachers and students about the textbook. 10 9th grade English teacher and 100 9th grade students participated in the study. For the analysis of the data obtained from the surveys, the SPSS program was used and evaluated proportionally in the frequency module. The responses to the 4 open-ended questions asked only to the teachers within the survey were grouped and examined according to the similar answers of the participants. The study also performed an independent-samples t-test to examine the differences between the participant teachers and students in terms of the common categories included in the surveys for each group. The results of this research study indicate that although the 9th grade English book examined is generally appropriate for the level of the students, it falls short in meeting the expectations of teachers and student users in some aspects. Therefore, the study concludes that the book requires some improvements to be a more effective teaching tool in English course.
Keywords: User opinions; Textbook evaluation; English 9 English textbook; in-use evaluation